Investigating the Aftermath of Terror: Fundamental Outcomes, Methodological Choices, and Future Directions. Issue 5 (June 2016) - Gradus, Jaimie L.; Marx, Brian P.; Sloan, Denise M.
Abstract : ABSTRACT: Acts of terrorism are becoming increasingly common throughout the world. These events represent a significant public health concern given the associated health consequences. Although it is clear that terrorist attacks have mental and physical health sequelae, the exact nature and prevalence of these consequences are unclear. Epidemiological research can play an important role in better understanding the mental and physical impact of terrorist attacks. In this editorial, we highlight recent epidemiological research on these terrorism-related health outcomes. We also provide suggestions for how future studies can build on the existing literature and describe ways in which epidemiological methods can be harnessed to extend the current literature. Lastly, we offer recommendations on how to best prepare communities for the aftermath of terrorist attacks, highlighting secondary intervention and prevention strategies. Overall, multilevel strategies are needed to adequately cope with the growing rise of terrorist acts, and these strategies will have to be reassessed as the nature of terrorist attacks changes.